A QUALITATIVE CONTENT STUDY "ANALYSIS OF NETIZEN SATISFACTION RESPONSES TOWARD MBG WEEKLY MENUS ON TIKTOK @SPPGCIKARET.KEBONPEDES : A QUALITATIVE CONTENT STUDY": A QUALITATIVE CONTENT STUDY - Nadila Jihan Tia Amelia; Euis Nurfitriyani; Sri Rahayu (Cakrawala Pedagogik, 2026)
Indonesia still face challenge triple burden of malnutrition , namely nutrition malnutrition?? more, and deficiency nutrition micro . As effort reach For the Golden Generation of 2045, the National Nutrition Agency (BGN) launched the Free Nutritious Meals Program (MBG). Research This aim For analyze response netizens to daily menu upload TikTok account @SPPGCikaret.Kebonpedes as form communication and promotion digital health . The research method used is qualitative descriptive with technique analysis content analysis and non - participatory observation to column comment over the past two weeks . The results of the study show that response audience divided become three category main : visual and menu variety , portions and taste , and education related to the MBG program. Findings show that visual aesthetics of the menu ( such as printed rice) character ) effective increase interest , but appear criticism about inequality quality between regions and lack of understanding public about shift The concept of "4 Healthy 5 Perfect " becomes "Fill My Plate". Conclusion study This emphasize that TikTok is an effective transparency medium , but SPPG needs to increase content education nutrition For complete content menu aesthetics . With Thus , society No only play a role as supervisor quality , but also get literacy proper nutrition? through digital platforms.